2009
DOI: 10.1155/2010/473798
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Lamivudine, Zidovudine and Abacavir in Tablet Dosage Forms by RP HPLC Method

Abstract: A simple, accurate and reproducible RP-HPLC method has been developed for the simultaneous determination of lamivudine, zidovudine and abacavir in tablet dosage forms. Chromatography was carried out on a HiQ Sil C 18 V column using a mobile phase consisting of 0.01 M potassium dihydrogenortho-phosphate (pH 3.0) and methanol (55:45 v/v) at a flow rate of 0.8 mL/min. The detection was made at 272 nm and stavudine was used as the internal standard for this study. The retention times for lamivudine, abacavir and z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…Previously few methods [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] are available for analysis of NVP in formulations and bulk drug.Ch Venkata Reddiah et al 20 reported one HPLC method for analysis of NVP and its impurities. While developing method at initial stage of the methoddevelopment trials done with NH 4 H 2 PO 4, Sodium per chlorate buffer solution at different pH and acetonitrile as solvent and C18 column but the separation of NVP and Impurity-Ais not good.…”
Section: Resultsmentioning
confidence: 99%
“…Previously few methods [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] are available for analysis of NVP in formulations and bulk drug.Ch Venkata Reddiah et al 20 reported one HPLC method for analysis of NVP and its impurities. While developing method at initial stage of the methoddevelopment trials done with NH 4 H 2 PO 4, Sodium per chlorate buffer solution at different pH and acetonitrile as solvent and C18 column but the separation of NVP and Impurity-Ais not good.…”
Section: Resultsmentioning
confidence: 99%
“…Although various methods like HPLC-UV, LC-MS/MS, HPTLC are available, these methods are expensive due to use of expensive detectors, costly solvents, columns and also more time needed to develop and validate the method. [14][15][16] The present IR spectroscopy method is a simple, rapid, accurate and cost effective analytical tool for AZT determination in tablet formulations.…”
Section: Discussionmentioning
confidence: 96%
“…First is the cost effectiveness of the system as methanol is the only organic solvent that has been used for the method development. Other systems mostly used acetonitrile as the major organic solvent and in some cased even used a combination of various organic solvents and phosphate buffer which would increase the operating cost if such analysis has to be performed in a regular basis [9,13,[18][19][20]. Methanol is cheaper, supposedly less damaging to health.…”
Section: Application Of the Analytical Methodmentioning
confidence: 99%
“…Various HPLC analysis methods have been reported for the analysis of different NRTIs and NNRTIs but there is lack of a simple, cost effective, definitive stability indicating method for analyzing the combination of 3TC, AZT and NVP that can be used in a FDC formulation [9][10][11][12][13]. Hence, the main objective of this study is to develop a simple and robust stability indicating HPLC-UV method for the simultaneous determination of the three analytes together with their possible degradants.…”
Section: Introductionmentioning
confidence: 99%